The effect of nanoclay on dust generation during drilling process of polyamide 6 nanocomposites - Sachse, Sophia; Silva, Francesco; Zhu, Huijun; Irfan, Adeel; Leszczynska, Agneska; Pielichowski, Krzysztof; Ermini, Valentina; Blazquez, Maria; Kuzmenko, Oleksandr; Njuguna, James A. K. (Hindawi Publishing Corporation, 2012)
During the past decade, polymer nanocomposites have emerged as a novel and rapidly developing class of materials and attracted considerable investment in research and development worldwide. However, there is currently a lack of information available in the literature on the nano and ultrafine particle emission rates from these materials. In this study, influence of nanoclay on mechanical drilling of PA6 composites, in terms of dust generation has been reported. With the help of real-time characterization, submicrometer-sized particles (5.6-512 nm) size distribution and number concentration emitted from polyamide 6/nanoclay composites during mechanical drilling is studied. Total particle concentration for the PA6/nanoclay composites was 20,000 cm-3, while unreinforced panel measured a total concentration of approximately 400,000 cm-3. While the airborne particle concentration for the PA6/ nanoclay composites was 20 times lower than for the PA6 matrix, the concentration of deposited nanoparticles doubled for the nanocomposite. The results clearly shows that more particles in the size range between 175-350 nm are generated, during drilling of the nanocomposites and this particles deposit in a shorter time. It is likely that the presence of nanoclay in some way retains the formation of high quantity of airborne particles and promotes particle deposition.